PARENTERAL VERSUS ORAL IRON THERAPY IN CHILDREN WITH IRON DEFICIENCY ANEMIA AND SAFETY PROFILE OF PARENTERAL IRON THERAPY (The Research of Medical Science Review, 2024)
Background: Iron deficiency anaemia is the most common cause of micronutrient deficiency in children worldwide and has an impact on the cognitive and physical development. Iron supplementation orally is the first choice, but the application is constrained by low patient compliance and adverse effect on gastrointestinal tract. Parenteral iron therapy has potential advantages, but its safety profile in paediatric patients is still a cause for concern.Aim: The purpose of this work is to establish the effectiveness and side effects of parenteral iron therapy compared to oral iron therapy in children with IDA.Methods: This study was a randomized controlled trial which was conducted at Combined Military Hospital (CMH) Quetta in the period between January 2023 to December 2023. Based on WHO sample size estimation for cross-sectional health facility-based studies, 400 children between two and twelve years of age with IDA were recruited and stratified according to their age and gender and then allocated to receive oral ferrous sulfate or parenteral iron sucrose. It was measured own levels of hemoglobin, ferritin and transferrin saturation at the baseline. The main findings were hemoglobin level returning to normal or improving at six weeks. The secondary endpoints included the rates of subject compliance and side effects experience. This information was then analyzed using the SPSS version 26 and the results were presented in color coded tables, bar graphs and pie charts when necessary.Results: The oral group had a silent suboptimal response with hemoglobin normalization in 75% of the patients in comparison to 95% in the parenteral group (p<0.001). The mean hemoglobin rise was higher in the parenteral group (3.5 ± 1.2 g/dL) than that of the oralgroup (2.1 ± 1.0 g/dL; p < 0.001). Compliance was significantly higher among the parenteral group (98%) than the oral group (60%, p<0.001). Side effects were tolerable; gastrointestinal side effects were reported in 20% of the oral group and hypotensive effects in 5% of the parenteral group.Conclusion: Parenteral iron therapy is more effective and has fewer side effects than oral iron therapy in children with IDA and better increases the rate of hemoglobin normalization and adherence. These observations provide evidence for the utility of parenteral iron replacement in situations where oral iron is either not well tolerated or not adhered to.